2005
DOI: 10.1172/jci26390
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in cell death: an innocent convict?

Abstract: The visualization of autophagosomes in dying cells has led to the belief that autophagy is a nonapoptotic form of programmed cell death. This concept has now been evaluated using cells and organisms deficient in autophagy genes. Most evidence indicates that, at least in cells with intact apoptotic machinery, autophagy is primarily a pro-survival rather than a pro-death mechanism. This review summarizes the evidence linking autophagy to cell survival and cell death, the complex interplay between autophagy and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

35
1,255
1
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,565 publications
(1,310 citation statements)
references
References 117 publications
35
1,255
1
8
Order By: Relevance
“…However, stimulated autophagy has been implicated in several types of cardiomyopathy 25. Autophagy is anti‐apoptotic and contributes to cellular recovery during brief myocardial ischaemia, but the subsequent reperfusion could cause excessive autophagy, which is considered cytotoxic and termed as class II programmed or autophagic cell death 6, 7, 8, 26. Our previous studies showed that inhibiting excessive autophagy could significantly decrease the infarct size and improve cardiac function after I/R‐induced myocardial injury 27, 28.…”
Section: Discussionmentioning
confidence: 99%
“…However, stimulated autophagy has been implicated in several types of cardiomyopathy 25. Autophagy is anti‐apoptotic and contributes to cellular recovery during brief myocardial ischaemia, but the subsequent reperfusion could cause excessive autophagy, which is considered cytotoxic and termed as class II programmed or autophagic cell death 6, 7, 8, 26. Our previous studies showed that inhibiting excessive autophagy could significantly decrease the infarct size and improve cardiac function after I/R‐induced myocardial injury 27, 28.…”
Section: Discussionmentioning
confidence: 99%
“…Lysosomes are major organelles involved in the degradation of damaged intracellular organelles (e.g., mitochondria) in autophagy, and they are fierce responders to oxidative stress. 49,50 Autophagy (cell "self-eating") usually occurs in nutrient or growth factor deprived cells. 49 It was shown that autophagy plays an instrumental role in serum deprivationinduced cell death in PC12 cells, and that lysosomes are involved in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagic cell death (also known as Type II programmed cell death to distinguish it from apoptosis or Type I programmed cell death) (20)(21)(22) has been described as a distinct form of cell death that differs from other death mechanisms such as apoptosis and necrosis. One example of autophagic cell death was caused by increased reactive oxygen species resulting from autophagic degradation of catalase (23).…”
mentioning
confidence: 99%